2012
DOI: 10.2337/db11-0550
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Common Genetic Variation to the Risk of Type 2 Diabetes in the Mexican Mestizo Population

Abstract: Several studies have identified nearly 40 different type 2 diabetes susceptibility loci, mainly in European populations, but few of them have been evaluated in the Mexican population. The aim of this study was to examine the extent to which 24 common genetic variants previously associated with type 2 diabetes are associated in Mexican Mestizos. Twenty-four single nucleotide polymorphisms (SNPs) in or near genes (KCNJ11, PPARG, TCF7L2, SLC30A8, HHEX, CDKN2A/2B, CDKAL1, IGF2BP2, ARHGEF11, JAZF1, CDC123/CAMK1D, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 45 publications
5
85
2
5
Order By: Relevance
“…Similarly, this polymorphism was found associated with diabetes in several works carried out in admixed populations from other Latin American countries (9,(23)(24)(25)28,29,31,32). However, Barros and cols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, this polymorphism was found associated with diabetes in several works carried out in admixed populations from other Latin American countries (9,(23)(24)(25)28,29,31,32). However, Barros and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among Latin American countries there are only reports on the association of TCF7L2 polymorphisms and T2DM from Colombia (23), Brazil (24)(25)(26)(27)(28) and Mexico (9,(29)(30)(31)(32). Latin American populations are characterized by high socioeconomic and genetic heterogeneity with varying degrees of ancestral population proportions from country to country, thus more studies are needed exploring the basis of T2DM susceptibility from these mixed populations.…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%
“…The association of rs2237892 polymorphism and rising T2DM incident risk proved former study result [2,4,[7][8][9][11][12][13][14][15][16][17][21][22][23][24]27,[29][30][31]36,[39][40][41][42][43][44][45][46]. East Asian, Southeast Asian and other region`s subgroup analysis also show the association still stable(OR=1.…”
Section: Main Discoversmentioning
confidence: 83%
“…As the associations between DM and the SNPs interrogated are generally similar across non-African populations [2229], we combined self-reported White, Hispanic, Asian, Native American, and Other women as one group (‘non-African-Americans’). Analyses were run separately for non-African-Americans (49 DM cases, 329 non-cases) and African-Americans (49 DM cases, 542 non-cases).…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, four genome-wide association studies (GWAS) identified multiple alleles associated with DM in predominately European populations [1721]. Replication studies in independent European, Asian, and Mexican populations have confirmed several of these DM risk variants [2229]. However, it appears that different signals are observed in African populations due to the greater degree of diversity in linkage disequilibrium (LD) patterns in populations of African descent [25, 3032].…”
Section: Introductionmentioning
confidence: 99%